(untitled) (Tribhuvan University Journal of Microbiology, 2019)
Objectives: The objective of this study was to evaluate Gene Xpert MTB/RIF Assay and anid fast staining (AFB) for rapid detection of Mycobacterium tuberculosis in specimen of patients suspected of pulmonary tuberculosis (PTB) and extra pulmonary tuberculosis (EPTB). Methods: A comparative cross-sectional study of 400 samples (PTB-365 and EPTB-35) of patients visiting National Tuberculosis Centre (NTC) was conducted from July 2018 to December 2018. Gene Xpert MTB/ RIF Assay, smear microscopy were performed under standard guideline inside biosafety cabinet class II. The result obtained from both the tests were analyzed using SPSS 20.0 software and Excel 2019. Results: Of the total samples, 18% (72/400) and 39% (156/400) were positive by AFB smear microscopy and Xpert MTB/RIF assay respectively. Prevalence of MTB positive was highest in the age group 35-44 years, 33 cases (17.74%) were detected in total, with a male to female ratio of 2.3:1. Pleural fluid, pus, and CSF fluid also yielded positive results with the Gene Xpert MTB/RIF assay accounting 1.28%, 0.64% and 1.28% of MTB positive case respectively. Rifampicin resistance was observed in 1.28% of the cases. Conclusion: The key findings of this study suggest that Gene Xpert test should be implemented as primary diagnostic test for PTB and EPTB.